Hubungan Antara Kepatuhan Hukum dan Kepercayaan Masyarakat terhadap Institusi Negara - Nabilah Azmi (Universitas Sains dan Teknologi Komputer, 2026)
This study examines the relationship between legal compliance and public trust in state institutions, addressing the limitations of linear approaches that treat trust solely as a determinant of compliance. Using a quantitative explanatory design, data were collected via a structured survey of adult respondents who had experience interacting with state institutions. Statistical analyses, including descriptive statistics, reliability testing, correlation analysis, and linear regression, were employed to evaluate the empirical relationship between the two constructs. The findings reveal a positive, statistically significant association between legal compliance and institutional trust, indicating that higher levels of legal compliance are associated with stronger public trust in state institutions. Beyond confirming existing theoretical assumptions, the results suggest that legal compliance may function not only as an outcome of institutional trust but also as a social mechanism that actively contributes to the formation and reinforcement of trust. This reciprocal relationship highlights the role of consistent and perceived fair compliance practices in strengthening institutional legitimacy. The study offers a relational perspective on legal compliance, enriching socio-legal scholarship and providing practical insights for policymakers seeking to enhance public trust through sustainable and non-coercive governance strategies.